Determinants of Non-paid Task Division in Gay-, Lesbian-, and Heterosexual-Parent Families With Infants Conceived Using Artificial Reproductive Techniques - Van Rijn - Van Gelderen, Loes; Ellis-Davies, Kate; Huijzer-Engbrenghof, Marijke; Jorgensen, Terrence D.; Gross, Martine; Winstanley, Alice; Rubio, Berengere; Vecho, Olivier; Lamb, Michael E.; Bos, Henny M. W. (Frontiers in Psychology, 2020)
Background: The division of non-paid labor in heterosexual parents in the West is usually still gender-based, with mothers taking on the majority of direct caregiving responsibilities. However, in same-sex couples, gender cannot be the deciding factor. Inspired by Feinberg’s ecological model of co-parenting, this study investigated whether infant temperament, parent factors (biological relatedness to child, psychological adjustment, parenting stress, and work status), and partner relationship quality explained how first-time gay, lesbian, and heterosexual parents divided labor (childcare and family decision-making) when their infants were four months and 12 months old. We also tested whether family type acted as a moderator. Method: Participants were drawn from [MASKED FOR REVIEW]. Only those who provided information about their biological relatedness (yes or no) to their child (N = 263 parents) were included. When infants were four months (T1), parents completed a password-protected online questionnaire exploring their demographic characteristics including work status and standardized online-questionnaires on task division (childcare and family decision-making), infant temperament, parental anxiety, parental depression, parental stress, and partner relationship satisfaction. When infants were 12-months-old (T2), parents provided information about task division and their biological relatedness to their children. Results: Linear mixed models showed that no factor explained the division of family decision making at T1 and T2. For relative time spent on childcare tasks at T1, biological relatedness mattered for lesbian mothers only: biologically related mothers appeared to spend more time on childcare tasks than did non-related mothers. Results showed that, regardless of family type, parents who were not working or were working part-time at T1 performed more childcare tasks at T1. This was still true at T2. The other factors did not significantly contribute to relative time spent on childcare tasks at T2. Conclusion: We had the opportunity to analyze the division of non-paid tasks in families where parenting was necessarily planned and in which gender could not affect that division. Although Feinberg’s model of co-parenting suggests that various factors are related to task division, we found that paid work outside the home was most important during the first year of parenthood in determining caregiving roles.